Effects of mercury surface temperature on the sodium abundance in its exosphere. (March 2022) - Rognini, E.; Mura, A.; Capria, M.T.; Milillo, A.; Zinzi, A.; Galluzzi, V.
Abstract: The link between the surface temperature of Mercury and the exosphere sodium content has been analyzed with the help of a thermophysical model giving soil temperatures coupled with an exospheric circulation model. The calculated exosphere abundance is maximum at perihelion when the temperature attains its maximum value. Another maximum is present at the perihelion; at this moment the temperature is lowest, and this secondary maximum can be explained with a mix of source, loss and transport processes. Key points: The link between the surface temperature of Mercury and the exosphere sodium abundance has been analyzed. A thermophysical model is being used coupled with an exospheric circulation model. The exospheric sodium abundance and distribution is strongly dependent on the surface temperature.